Thinking Together : The Friendship between Ernst Bloch and Georg Lukács - Galcerán Huguet, Montserrat (Analysis. Journal of Philosophical Research, 2023)
This article deals with the friendship between two important Marxist thinkers, E. Bloch (1885-1977) and G. Lukács (1885-1971), and how this friendship influenced their works, especially the writings of their youth, although echoes of it can be found in their mature works. From this dialogue emerges a new way of understanding the category of "possibility" which contrasts with the classical category of "historical necessity". Translated with DeepL